Family Business Succession The Final Test of Greatness - Aronoff, C. (A Family Business Publication, 2011)
Helps to prepare for passing the family business on to the next generation. Leaders will learn how to create a succession plan; how to develop opportunities for succession candidates; how to build consensus with the family and leaders on succession plans and finally leaders will learn when and how to let go of their own role in the business.